Evolution of SILS Cholecystectomy in the Caribbean: The Direct Transfascial Puncture Technique Using Conventional Instruments without Working Ports - Shamir O. Cawich; Dexter Thomas; Dale Hassranah; Vijay Naraynsingh (Case Reports in Surgery)
Introduction. Single incision laparoscopic cholecystectomy (SILC) has become accepted as an alternative to conventional multiport cholecystectomy. However, SILC is still limited in applicability in low resource centres due to the expense associated with specialized access platforms, curved instruments, and flexible scopes. Presentation of Case. We present three cases where a modified SILC technique was used with conventional instruments and no working ports. The evolution of this technique is described. Discussion. In order to contain cost, we used conventional instruments and three transfascial ports placed in an umbilical incision, but we noted significant instrument clashes that originated at the port platforms. Therefore, we modified our technique by omitting ports for the working instruments. The technique allowed us to exchange instruments as necessary, maximized ergonomics, and prevented collisions from the bulky port platforms. Finally, the puncture left by the instrument alone did not require fascial closure at the termination of the procedure. Conclusion. The direct transfascial puncture using conventional laparoscopic instruments without working ports is a feasible option that minimizes cost and increases ergonomics.